2008
DOI: 10.1007/s11605-008-0706-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-blinded Randomized Trial of Mechanical Bowel Preparation for Colon Surgery with Primary Intraperitoneal Anastomosis

Abstract: Our final analysis shows that a single surgeon will not have a higher rate of either surgical-site infection or anastomotic failure if he/she routinely omits preoperative mechanical bowel preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 24 publications
1
32
0
1
Order By: Relevance
“…Five studies [4,6,21,23,24] reported the colonic surgery results with or without MBP. There were no statistical differences between the groups for all the outcomes considered.…”
Section: Colonic Vs Rectal Surgerymentioning
confidence: 99%
“…Five studies [4,6,21,23,24] reported the colonic surgery results with or without MBP. There were no statistical differences between the groups for all the outcomes considered.…”
Section: Colonic Vs Rectal Surgerymentioning
confidence: 99%
“…Superficial surgical site infections were more frequent in the MBP group; however, the difference was not statistically significant (MBP = 24.6%, non-MBP = 17.2%; NS). Anastomotic failure rates were also not significantly different (MBP = 6.2%, non-MBP = 4.7%; NS), supporting the omission of MBP in ECS [9]. In the RCT published by Bucher et al [10] in 2005, the infectious complications (anastomotic dehiscence and surgical site infections) were significantly higher among the patients who received MBP before ECS.…”
Section: Resultsmentioning
confidence: 79%
“…Likewise, there was no significant difference in wound infections between the two groups (difference 0.6%, 95% confidence interval 3.2-4.4%, P = 0.82). The next RCT published by Pena-Soria et al in [9] 2008 was a single-blinded randomized trial involving 129 patients (65 in MBP group). Superficial surgical site infections were more frequent in the MBP group; however, the difference was not statistically significant (MBP = 24.6%, non-MBP = 17.2%; NS).…”
Section: Resultsmentioning
confidence: 99%
“…From other surgical specialties, 23 studies met the inclusion criteria in colorectal surgery comparing MBP with no MBP: 13 RCTs (4932 patients) [57,[59][60][61][62][63][65][66][67][68][69][70][71], 2 prospective cohort studies (418 patients) [72,74], and 8 retrospective cohort studies (5141 patients) [75,78,81,[83][84][85][86]89]. All studies included only elective surgery; however, they were heterogeneous in the types of surgery performed (ileocolic, colocolic, and colorectal) and mode of surgery (laparoscopic or open surgery, or combination of both).…”
Section: Resultsmentioning
confidence: 99%
“…Among the high-quality studies evaluating patient complications, 3 studies (total 490 colorectal patients) found increased complications from MBP [59,62,66], which included increased rates of anastomotic dehiscence (p 5 .05) [62], increased infectious abdominal complications (p 5 .028) [66], and overall surgical infectious complications (20% vs 11.3%, p 5 .05) [59]. The complications were not subcategorized according to the Clavien-Dindo classification system.…”
Section: Resultsmentioning
confidence: 99%